The descriptive phenomenological method in psychology : a modified Husserlian approach - Giorgi, Amedeo, 1931- (Pittsburgh, Pa. : Duquesne University Press, 2009)
"Discusses the phenomenological foundations for qualitative research in psychology which operates out of the intersection of phenomenological philosophy, science, and psychology; challenges long-standing assumptions about the practice of grounding the science of psychology in empiricism and asserts that the broader philosophy of phenomenological theory of science permits more adequate psychological development"--Provided by publisher.
Includes bibliographical references (p. 217-228) and index.
Keywords: Phenomenological psychology; Psychology -- Research